2021
DOI: 10.3390/land10020221
|View full text |Cite
|
Sign up to set email alerts
|

Landscape and Tourism as Tools for Local Development in Mid-Mountain Rural Areas in the Southeast of Spain (Castilla-La Mancha)

Abstract: The modernization of economic activities in mountain areas is conditioned by the physical characteristics of the territory, the weight of activities related to the primary sector, infrastructure deficits, low population density, as well as the declining and ageing population. The response to this situation has involved implementing a certain degree of functional diversification. One of the aspects that has assisted in the expansion of the tertiary sector is leisure and recreational activities. Rural tourism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…A study conducted in the Lake Tana region in Ethiopia also found that geosites combining a local geo-feature and a viewpoint were rated highest for their scenic beauty [16]. In addition, a survey of 582 visitors in the Albacete mountains (Spain), indicated that among the components that shape the character of the landscape (such as relief, water, vegetation, rural habitat, the combination of human and natural environments, climate, rural landscape, environmental quality and wildlife), the most important landscape component (as indicated by the rankings of these components by the respondents) was relief which includes mountains, gorges and valleys [108]. Such landscape components combine a local geo-feature and a viewpoint, and hence also support our finding.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the Lake Tana region in Ethiopia also found that geosites combining a local geo-feature and a viewpoint were rated highest for their scenic beauty [16]. In addition, a survey of 582 visitors in the Albacete mountains (Spain), indicated that among the components that shape the character of the landscape (such as relief, water, vegetation, rural habitat, the combination of human and natural environments, climate, rural landscape, environmental quality and wildlife), the most important landscape component (as indicated by the rankings of these components by the respondents) was relief which includes mountains, gorges and valleys [108]. Such landscape components combine a local geo-feature and a viewpoint, and hence also support our finding.…”
Section: Discussionmentioning
confidence: 99%
“…They are therefore of great importance in economic, social and environmental terms [24][25][26][27]. The open landscape of rural areas is important in terms of tourism activities, especially in the case of a variety of mountainous regions [28][29][30][31][32]. Noted that these aspects contribute often to considerations of multifunctional rural development and landscape transformation at the local level [33][34][35][36][37][38][39].…”
Section: Literature Review 21 the Agritourism Farm In The Context Of ...mentioning
confidence: 99%
“…En cuanto al número de habitantes, Extremadura se posiciona para ese año en decimotercer lugar con 1 063 987 residentes; sin embargo, las dos provincias que la conforman destacan por ser las más extensas del país en cuanto a superficie, superando los 40 000 kilómetros cuadrados. No obstante, en la región extremeña solamente siete de sus trescientos ochenta y ocho municipios superan los 20 000 habitantes, tamaño este de evidente importancia dado que es capaz de aglutinar diversos servicios y equipamientos básicos (Molinero, 2019;Abellán & García-Martínez, 2021;Bayona-i-Carrasco & Gil-Alonso, 2013). De estos, únicamente dos de ellos se localizan en la provincia cacereña (Plasencia y Cáceres), mientras que los cinco restantes se emplazan en la pacense (Villanueva de la Serena, Almendralejo, Don Benito, Mérida y Badajoz).…”
Section: Introductionunclassified